ACUTE MYOCARDITIS SECONDARY TO DENGUE INFECTION IN A YOUNG FEMALE PATIENT: A CASE STUDY - SIDDEM CHAKRADHAR; VAISHNAVI RAVI; SWARNALINGAM THANGAVELU; KARTHIK MANI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Dengue fever is a common mosquito-borne viral infection, especially in tropical regions where it is endemic. While most cases present with typical symptoms like fever and musculoskeletal pain, severe dengue can lead to rare but serious complications, including myocarditis and cardiogenic shock. This case report describes a young female who developed dengue myocarditis with cardiogenic shock, reemphasizing the wide spectrum of complications in dengue. Through this case and a review of relevant literature, we discuss the clinical features, diagnostic approach, treatment, and prognosis for patients with dengue myocarditis.